Efektivitas penggunaan elearning madrasah dalam pembelajaran jarak jauh di MTSN 1 Kota Malang pada masa covid -19 - Widodo, Mohamad Kholish (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The Ministry of Religion of the Republic of Indonesia made an innovation to help the distance learning process by launching a free application that can be accessed by all teachers and students in madrasas ranging from RA, MTs, and MA throughout Indonesia, namely E-learning madrasas. This study aims to describe the effectiveness of using madrasa e-learning in distance learning at MTsN 1 Malang City during the covid-19 period. The reason for choosing this institution as the research location is because MTsN 1 Malang City is a pilot madrasa in Indonesia and one of the madrasas that uses e-learning madrasas. This research uses descriptive qualitative method. Data retrieval was carried out naturally using a questionnaire filling technique with open questions, observations when using e-learning and documentation. To check the validity of the data, the researcher consulted the results of the study, the participants used sources triangulation techniques and methods. Data analysis was carried out following general qualitative research procedures, starting with data collection, coding, classification, subtraction, and inference. This study found the weaknesses and strengths of madrasa e-learning, the effectiveness of its use in distance learning, its use for teachers and students, and solutions to overcome the obstacles of using madrasa e-learning. This research can contribute to the effective use of madrasa e-learning to support the effectiveness of distance learning and can be used as an editor for other institutions.